Comparison of fixed 10 mCi and 15 mCi iodine-131 doses for the treatment of graves' disease: 11 year study [Graves hastaliǧi tedavisinde sabit 10 mCi ve 15 mCi i̇yot-131 dozlarinın karşılaştırılmasi: 11 yıllık tecrübe] - (:unkn) unknown (Marmara University, 2011)
Objectives: Fixed dose Iodine-131 (RAI) treatment is a simple method which does not obviate sophisticated calculations. In this study, we compared the results of fixed 10mCi and 15 mCi RAI treatment. Patients and Methods: In this study we included 55 patients who received fixed 10 mCi and 15 mCi RAI treatment between 1997-2008 years and were followed for at least 2 years. Then we analyzed the results as successful (euthyroid, hypothyroid) and unsuccessful (persistant hyperthyroid) treatment rates and other parameters that could have affected the results. Results: The success rate in patients who received 10 mCi RAI was 87% (euthyroid 9.1%, hypothyroid 78.2%). The success rate in patients who received 15 mCi RAI was 100% (hypothyroid). There is no statistically significant difference between these groups except mean propythiouracil doses (10 mCi: 190 mg, 15 mCi: 350 mg, p <0.05). Conclusion: Fixed 10 mCi and 15 mCi RAI dose applications were both successful in the treatment of Graves' disease. Albeit at a lower rate persistent hyperthyroidism can be seen in patients given fixed 10mCi RAI dose.
Keywords: Fixed dose; Graves' disease; Iodine-131; Therapy